An integrated n-Si/BiVO4 photoelectrode with an interfacial bi-layer for unassisted solar water splitting. Issue 8 (6th February 2023) - Wang, Shujie; Feng, Shijia; Liu, Bin; Gong, Zichen; Wang, Tuo; Gong, Jinlong
Abstract : This paper describes an interfacial bi-layer for the integration of Si and BiVO4, predicted to achieve record total H2 production for unbiased solar water splitting. Abstract : Integrated n-Si/BiVO4 is one of the most promising candidates for unbiased photoelectrochemical water splitting. However, a direct connection between n-Si and BiVO4 will not attain overall water splitting due to the small band offset as well as the interfacial defects at the n-Si/BiVO4 interface that severely impede carrier separation and transport, limiting the photovoltage generation. This paper describes the design and fabrication of an integrated n-Si/BiVO4 device with enhanced photovoltage extracted from the interfacial bi-layer for unassisted water splitting. An Al2 O3 /indium tin oxide (ITO) interfacial bi-layer was inserted at the n-Si/BiVO4 interface, which promotes the interfacial carrier transport by enlarging the band offset while healing interfacial defects. When coupled to a separate cathode for hydrogen evolution, spontaneous water splitting could be realized with this n-Si/Al2 O3 /ITO/BiVO4 tandem anode, with an average solar-to-hydrogen (STH) efficiency of 0.62% for over 1000 hours.